2000
DOI: 10.2136/sssaj2000.642450x
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Water Flow in a Layered Soil I. Effects of a Stable Water‐Repellent Layer

Abstract: The development of preferential water flow in a soil profile can cause accelerated movement of pollutants to the groundwater thus reducing groundwater quality. This study investigated the effects of a stable water‐repellent soil layer on the development of unstable water flow in a homogenous profile. Stable water‐repellent soil is defined as one whose degree of water repellency does not change with time after contact with water. The effects of water entry pressure (hp), water‐repellent layer depth (L) and dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…In many cases, the surface layer was water repellent while the subsoil was wettable. Carillo et al (2000) found that stable flow occurred when the water flux through a water repellent layer exceeded the saturated hydraulic conductivity of the underlying wettable layer. Wang et al (1998) asserted that in water repellent sands, the wetting front stabilises when the ponding depth exceeds the waterentry value of the hydrophobic medium.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the surface layer was water repellent while the subsoil was wettable. Carillo et al (2000) found that stable flow occurred when the water flux through a water repellent layer exceeded the saturated hydraulic conductivity of the underlying wettable layer. Wang et al (1998) asserted that in water repellent sands, the wetting front stabilises when the ponding depth exceeds the waterentry value of the hydrophobic medium.…”
Section: Introductionmentioning
confidence: 99%
“…The former type of fingers generally occurs in clay and peat soils with well‐defined macropore or mesopore networks. Although instability‐driven fingers have been found in water‐repellent soils (Ritsema and Dekker, 1994, 2000; Bauters et al, 1998; Carrillo et al, 2000a). There are many factors that induce finger‐like pathways, including hysteresis (Ritsema et al, 1998), SWR, soil structure, different head pressures on the soil surface from a point source water application (Wallach and Jortzick, 2008), and so on.…”
mentioning
confidence: 99%
“…Qualitative tests performed by dropping a definite amount of water droplets on the cake surface showed that the droplet was sucked immediately into the cake when using wet peat, due to the capillary force of the pores, whereas in the experiments using dried peat, the droplet initially remained on the top of the cake for seconds or even minutes. This water repellence has been observed and investigated mainly for soil [14]. Water repellence is believed to correlate with the material composition of the soil such as humic acid, wax, etc., as well as the moisture content of the soil.…”
Section: Influence Of Predryingmentioning
confidence: 99%